Some Aspects of Serbian Religious Development in the Eighteenth Century - Jelavich, Charles (Church history, 1954)
The eighteenth century was an era of conflict and radical change within the Serbian church. After the establishment of Ottoman control in the Balkan peninsula, the Serbian nation remained united solely by the bonds of the church. It was the center of life and the unchallenged leader of the community. However, in the eighteenth century new ideals and new loyalties emerged which threatened the position of predominance previously enjoyed by the church. Religious nationalism gradually gave way before secular nationalism as the ideas of the enlightenment took root among the Serbs living within the Habsburg empire, until by the end of the century the church as an instrument of national unification had been relegated to a position of secondary importance. Moreover, the change was the result not only of the absorption of western thought by the Serbian intellectuals, but also of the rivalries of the Christian churches in the Balkans, a conflict whose roots are to be found in this century.